2018
DOI: 10.1159/000493406
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin/GPR54 System: What Do We Know About Its Role in Human Reproduction?

Abstract: Kisspeptin is involved in the control of human reproduction bridging the gap between the sex steroid levels and feedback mechanisms that control the gonadotropin releasing hormone (GnRH) secretion; however, studies considering this peptide and infertility are limited. We conducted a review and critical assessment of available evidence considering kisspeptin structure, physiology, function in puberty and reproduction, its role in assisted reproduction treatments, kisspeptin dosage and the impact on KISS1 and GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 105 publications
1
84
0
9
Order By: Relevance
“…107 A picture emerges that the Me contains subpopulations of specific neurons identifiable by sexually dimorphic expression of genes that integrate olfactory inputs to drive specific behaviors. 110,111 Kisspeptin-synthesizing neurons are also found in the Me, as are neurons that express kisspeptin receptor, and studies have shown that kisspeptin signaling is essential for various aspects of sexual function, including sexual behaviors in both sexes and for olfactory-mediated behaviors. 108,109 Another particularly compelling example involves kisspeptin, a neuropeptide localized mostly in neurons in the hypothalamus that plays a key regulatory role in reproductive physiology.…”
Section: Medial Amygdalamentioning
confidence: 99%
See 1 more Smart Citation
“…107 A picture emerges that the Me contains subpopulations of specific neurons identifiable by sexually dimorphic expression of genes that integrate olfactory inputs to drive specific behaviors. 110,111 Kisspeptin-synthesizing neurons are also found in the Me, as are neurons that express kisspeptin receptor, and studies have shown that kisspeptin signaling is essential for various aspects of sexual function, including sexual behaviors in both sexes and for olfactory-mediated behaviors. 108,109 Another particularly compelling example involves kisspeptin, a neuropeptide localized mostly in neurons in the hypothalamus that plays a key regulatory role in reproductive physiology.…”
Section: Medial Amygdalamentioning
confidence: 99%
“…108,109 Another particularly compelling example involves kisspeptin, a neuropeptide localized mostly in neurons in the hypothalamus that plays a key regulatory role in reproductive physiology. 110,111 Kisspeptin-synthesizing neurons are also found in the Me, as are neurons that express kisspeptin receptor, and studies have shown that kisspeptin signaling is essential for various aspects of sexual function, including sexual behaviors in both sexes and for olfactory-mediated behaviors. [112][113][114] In the rodent, projections from the AOB, but not the MOB, contact Me kisspeptin neurons, 115 and in female mice, inputs from the AOS, and not the MOS, provide olfactory information to kisspeptin neurons in the periventricular hypothalamus that are essential for female sexual behavior.…”
Section: Medial Amygdalamentioning
confidence: 99%
“…It is also possible that each colony has its own unique chemical cue of colony size. We favour the idea that something as important as coordinating developmental transitions would be shared across colonies, akin to reproductive hormones in humans, such as the kisspeptin/GPR54 system (Trevisan et al ., ). There is, however, the possibility that each colony has a unique colony‐level trigger that changes as the colony grows.…”
Section: Discussionmentioning
confidence: 97%
“…By injecting kisspeptin-10 into sheep's brain, a large amount of GnRH can be directly observed in the cerebrospinal fluid, accompanied by an increase in LH [56] . This effect is caused by the Kiss-1 encoded product, kisspeptin, which binding to the GPR54 [57] . GPR54 is a G protein-coupled receptor in the rhodopsin family [58] .…”
Section: Discussionmentioning
confidence: 99%